Post hemorrhagic hydrocephalus and neurodevelopmental outcomes in a context of neonatal intraventricular hemorrhage: an institutional experience in 122 preterm children - Vianney Gilard; Alexandra Chadie; François-Xavier Ferracci; Marie Brasseur-Daudruy; François Proust; Stéphane Marret; Sophie Curey (BMC, 2018)
Abstract Background Intraventricular hemorrhage (IVH) is a frequent complication in extreme and very preterm births. Despite a high risk of death and impaired neurodevelopment, the precise prognosis of infants with IVH remains unclear. The objective of this study was to evaluate the rate and predictive factors of evolution to post hemorrhagic hydrocephalus (PHH) requiring a shunt, in newborns with IVH and to report their neurodevelopmental outcomes at 2 years of age. Methods Among all preterm newborns admitted to the department of neonatalogy at Rouen University Hospital, France between January 2000 and December 2013, 122 had an IVH and were included in the study. Newborns with grade 1 IVH according to the Papile classification were excluded. Results At 2-year, 18% (n = 22) of our IVH cohort required permanent cerebro spinal fluid (CSF) derivation. High IVH grade, low gestational age at birth and increased head circumference were risk factors for PHH. The rate of death of IVH was 36.9% (n = 45). The rate of cerebral palsy was 55.9% (n = 43) in the 77 surviving patients (49.4%). Risk factors for impaired neurodevelopment were high grade IVH and increased head circumference. Conclusion High IVH grade was strongly correlated with death and neurodevelopmental outcome. The impact of an increased head circumference highlights the need for early management. CSF biomarkers and new medical treatments such as antenatal magnesium sulfate have emerged and could predict and improve the prognosis of these newborns with PHH.